Kebijakan Batasan Kekuasaan Eksekutif dan Legislatif dalam Amademen Undang-Undang Dasar 1945 pada Sistem Pemerintahan - Edwin Hendrik; Subekti Subekti; M. Syahrul Borman (Majelis: Jurnal Hukum Indonesia, 2024)
The amendment to the 1945 Constitution is an important milestone in the history of the Indonesian constitution that aims to improve the system of government and maintain the balance of power between the executive and legislative. This study aims to analyze the policy of limiting executive and legislative powers implemented through the amendment to the 1945 Constitution, and its implications for the system of government in Indonesia. The research method used is normative research with a qualitative approach, through literature studies and analysis of constitutional documents and relevant laws and regulations. Data were obtained from various sources, including the text of the 1945 Constitution before and after the amendment, academic literature, and the results of interviews with constitutional law experts. The results of the study indicate that the amendment to the 1945 Constitution has brought significant changes in the limitation of executive and legislative powers. Among them, the amendment introduced a stronger checks and balances mechanism, clarified the functions and authorities of each state institution, and set limits on the presidential term of office to prevent absolute power.